2023
DOI: 10.1002/jmv.28403
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial profiles and their antibiotic resistance background in superinfections caused by multidrug‐resistant bacteria among COVID‐19 ICU patients from southwest Iran

Abstract: This study investigated the bacterial causes of superinfections and their antibiotic resistance pattern in severe coronavirus disease 2019 (COVID‐19) patients admitted to the intensive care unit (ICU) of Razi Hospital in Ahvaz, southwest Iran. In this cross‐sectional study, endotracheal tube (ETT) secretion samples of 77 intubated COVID‐19 patients, confirmed by reverse transcription‐quantitative polymerase chain reaction, were investigated by standard microbiology test and analytical profile index kit. Antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
3
1
Order By: Relevance
“…The possible reason was that we focused on older people. Another study reported that 72.7% of the COVID-19 ICU patients had secondary infection (Akrami et al, 2023), which was higher than reported in this study. The possible reason might be due to widespread usage of mechanical ventilator that expose patients to infection.…”
Section: Discussioncontrasting
confidence: 72%
“…The possible reason was that we focused on older people. Another study reported that 72.7% of the COVID-19 ICU patients had secondary infection (Akrami et al, 2023), which was higher than reported in this study. The possible reason might be due to widespread usage of mechanical ventilator that expose patients to infection.…”
Section: Discussioncontrasting
confidence: 72%
“…Also, in Iran, a study conducted on COVID-19 patients admitted to the intensive care unit (ICU) revealed that the Gram-negative bacteria were more predominant than the Gram-positive pathogens. Klebsiella pneumoniae (28.4%) was the most common isolate followed by Staphylococcus aureus (22.4%) [30]. But Gram-positive organisms represented the majority of infections found in a study in both the blood and sputum cultures in USA [31].…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, a study in Iran revealed increased concomitant infections by MDR bacteria (68.7%, 46/67) among COVID-19 patients. More than 70.0% of the Gram-positive and Gram-negative isolates were resistant to most antibiotics, including fluoroquinolone, carbapenems, and cephalosporins [30]. Also, in Saudi Arabia, ICU patients which had coinfections with Gram-negative bacteria, showed high resistance to all tested antibiotics except colistin [32].…”
Section: Discussionmentioning
confidence: 99%
“…it may lead to severe respiratory distress syndrome and presence linked and more severe kidney, damage prolonged artificial breathing, and longer I.C.U. admission (Akrami et al, 2023).…”
Section: Resultsmentioning
confidence: 99%